Peran Job Description Terhadap Kinerja Karyawan Pada PT. Domas Sawit Inti Perdana - Nur Hazizah; Budi Dharma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Zakat Management Details the Management of Zakat Given from an Institution to Prospective Zakat Recipients Required in Distributing Zakat. To ensure that the practice of zakat is in accordance with sharia principles, the management of zakat distribution is carried out. In this research, the author tries to make research and analysis regarding the management of zakat distribution at the North Sumatra Regional Unit PLN Baitul Mall Foundation which includes planning, organizing, distributing zakat, as well as monitoring the validity of muzaki when receiving zakat, such as the validity of muzaki in terms of where one lives and the family. , and education. The results of this study will show that the North Sumatra Regional Unit PLN Baitul Mall Foundation has become a leading organization for distributing ZIS (zakat, infaq, and shadaqoh) in the PT PLN (Persero) environment in order to make mustahik become muzaki.